Study on binder system of CO2-cured phenol-formaldehyde resin used in phenol-formaldehyde resin used in foundry - Liu Weihua; Li Yingmin; Qu Xueliang (China Foundry, 2008)
A new aqueous alkaline resol phenol-formaldehyde resin has been prepared from phenol and formaldehyde using NaOH as catalyst; the optimum synthetic process has been determined. With addition of some cross-linking agents, after passing carbon dioxide gas through the resin bonded sand, high as-gassed strength and 24 h strength are achieved. The bonding bridge of the resin bonded sand fracture has been analyzed by using SEM.